2018
DOI: 10.1159/000494032
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Copper and Serum Lipids in Adults

Abstract: Background: As an essential trace element, copper has been considered to play an important role in lipid metabolism. However, the associations of serum copper with lipid concentration and dyslipidemia are still controversial. Methods: We used the 2011–2014 National Health and Nutrition Examination Survey to examine the relationship between serum copper and lipid concentration among participants aged 20 years and older. Multivariate linear regression was conducted to estimate the differences in the level of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
5
20
1
2
Order By: Relevance
“…Furthermore, the current study reported an increase in BMI, PR, TC, HDL, and HbA1c with the increase in Cu circulating levels. Similar results were indicated for age, BMI, TC, and HDL in another study [ 45 ]. Cu level was reported to be significantly higher in hypertensive patients [ 50 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, the current study reported an increase in BMI, PR, TC, HDL, and HbA1c with the increase in Cu circulating levels. Similar results were indicated for age, BMI, TC, and HDL in another study [ 45 ]. Cu level was reported to be significantly higher in hypertensive patients [ 50 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…A cohort study found no association between low and high HDL and Cu when adjusted for sex and BMI [ 91 ]. Also, no association was found between low HDL and serum Cu levels after adjustment for multiple variables in another study [ 45 ]. Cu deficiency can cause damage to cardiovascular morphology and physiology due to Cu-dependent enzyme variation, peroxidation as a result of free radical accumulation due to distress to the Cu antioxidant effect, protein glycation due to glucose accumulation and abnormal carbohydrate metabolism, and impaired protein structure and function [ 92 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A associação entre o consumo de cobre e menor TG apesar de não ter sido significativa, Fan, Zhang e Bu (2017) e Wolide, Zawdie, Alemayehu e Tadesse (2017) encontraram resultados semelhantes. Shoji, et al (2016); Song, Wang, Zhang (2018) encontraram relação entre as concentrações de cobre e alterações lipídicas.…”
Section: Discussionunclassified
“…Apesar de não terem sido registrados dados consistentes em relação a esse elemento, sabe-se que o cobre é um elemento essencial e importante componente de enzimas antioxidantes que atuam na proteção contra os radicais livres no organismo e que desequilíbrios no seu metabolismo podem resultar em hipercolesterolemia e aumento do estresse oxidativo (Song, Wang, Zhang, 2018).…”
Section: Discussionunclassified